The relationship between urinary and plasma levels of tumor necrosis factor alpha and various stages of chronic kidney disease in patients with type II diabetes mellitus - Alireza Soleimani; Maryam Soleimani; Forouz Farzadnejad; Mohammadreza Tamadon (Society of Diabetic Nephropathy Prevention, 2020)
Introduction: The concept of diabetic nephropathy, as a metabolic disease, is now being replaced by chronic low-grade inflammatory disease. Tumor necrosis factor alpha (TNF-α) is a proinflammatory cytokine that plays an important role in the pathogenesis and clinical outcomes of diabetic nephropathy. Objectives: This study aimed to determine the relationship between plasma and urinary levels of TNF-α and chronic kidney disease (CKD) in patients with type 2 diabetes mellitus. Patients and Methods: In this descriptive-analytical study, patients with type 2 diabetes mellitus who referred to the endocrine clinic in Kashan (2016) were enrolled in the study and their clinical and laboratory data were recorded. Albumin/creatinine ratio (ACR) and glomerular filtration rate (GFR) were calculated. The patients were divided into three groups based on their GFR. Serum and urinary levels of TNF-α were determined by ELISA and were compared between the studied groups. Results: A total of 128 patients were evaluated. Of all, 35 patients (27.3%), 39 patients (30.4%), and 54 patients (42.3%), respectively, were suffering from stage 1, stage 2, and stage 3 CKD. The plasma levels of TNF-α in patients with stage 1, 2, and 3 CKD, were 66.20 ± 33.27 pg/mL, 67.47 ± 42.98 pg/mL, and 77.32 ± 47.23 pg/mL respectively, since the difference among them was not significant (P= 0.417). In addition, the urinary levels of TNF-α in patients with stage 1, 2, and 3 CKD, respectively, were 88.18 ± 26.66 pg/mL, 97.41 ± 57.76 pg/mL, and 101.18 ± 60.47 pg/mL, since no significant difference was observed between the three groups (P=0.957). Conclusion: Based on the results of this study, with changing the stage of CKD, the serum and urinary levels of the TNF-α increases too, although this increase is not significant. Moreover, the plasma and urinary levels of the TNF-α have a direct and significant relationship with each other. It is recommended to conduct further studies in this field.